PENGARUH PERTUMBUHAN EKONOMI, SHARE SEKTOR INDUSTRI DAN PERTANIAN SERTA TINGKAT JUMLAH ORANG YANG BEKERJA TERHADAP KETIMPANGAN WILAYAH ANTAR KABUPATEN/KOTA DI JAWA TENGAH TAHUN 2002-2010 - Benedictus Riandoko Adi Kurniawan; FX. Sugiyanto (Universitas Diponegoro, 2013)
Inequality is a development problem that cannot be eliminated, especially in developing countries. Regional inequality in Central Java Province depend on nature and demographical capability from each region in Central Java Province.This study aimed to calculate the level of inequality in the area of Central Java Province, proving Kuznets hypothesis, and to analyze the influence of independent variables growth, share from agriculture and industrysector and rate of employment on regional disparities in the Central Java Province in the period 2002 to 2010. This study uses secondary data which was obtained from Badan Pusat Statistik (BPS) Central Java Province. This research method are analysis descriptive statistics and regression analysis with panel datawhich use fixed effect model. The results from this studies conclude that regional inequality in Central Java Province still high enough and Kuznets hypoyhesis proved. Based on the results of the regression, share agriculture and industry sector variables have positive and significant of regional disparities in Central Java Province. Growth variables has positive but not significant impact on regional disparities, and rate of employment has negative but not significant impact on regional disparities in Central Java Province.